2009
DOI: 10.1177/1075547008328797
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Step Flow of Influence?

Abstract: In this article, we review concepts, measures, and strategies that can be applied to opinion-leader campaigns on climate change. These campaigns can be used to catalyze wider political engagement on the issue and to promote sustainable consumer choices and behaviors. From past research, we outline six relevant categories of self-designated opinion-leaders, detailing issues related to identification, recruitment, training, message development, and coordination. We additionally analyze as prominent initiatives A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(85 citation statements)
references
References 26 publications
2
79
1
3
Order By: Relevance
“…However, doing outreach for scientists is generally considered as time-consuming and not enough rewarded in term of career advancement by research funding agencies. BD issues would largely benefit from engagement of a public figure that embrace the cause, as Al Gore did for the CC issue (Nisbet and Kotcher, 2009). …”
Section: How Can We Explain a Biodiversity Communication Deficit?mentioning
confidence: 99%
“…However, doing outreach for scientists is generally considered as time-consuming and not enough rewarded in term of career advancement by research funding agencies. BD issues would largely benefit from engagement of a public figure that embrace the cause, as Al Gore did for the CC issue (Nisbet and Kotcher, 2009). …”
Section: How Can We Explain a Biodiversity Communication Deficit?mentioning
confidence: 99%
“…News media are important ways that individuals learn about climate change (Brüggemann, 2017), at the same time that opinion leaders hold sway over public sentiment on climate issues (Nisbet & Kotcher, 2009). Social media apps and platforms are increasingly the hybrid media spaces (see Chadwick, 2017) where individuals are encountering news and information on a diverse range of topics, including climate issues.…”
Section: Discussionmentioning
confidence: 99%
“…Given that media are a way in which individuals often get information about climate change and that past research has shown climate change opinion leaders (e.g., former US Vice President Al Gore) play an influential role in opinion formation on climate issues, such as promoting pro-environmental behaviors through digital campaigning (see Nisbet & Kotcher, 2009), we chose to develop a sample which would allow us to compare visual framing across climate stakeholder categories during the climate talks. We built our sample of tweets for inclusion in this study around climate stakeholder categories, rather than hashtags or keywords, to study the relative prominence of posts about the climate summit, compared to non-COP21 or climate change posts, during the climate talks as a focusing event by these key actor types taking part in, or reporting on, the negotiations.…”
Section: Data Collectionmentioning
confidence: 99%
“…Wine consumers have been studied to use risk relievers such as: (1) opportunity to taste (Johnson & Bruwer, 2004;Mitchell & Greatorex, 1989), (2) personal recommendations (Nisbet & Kotcher, 2009), (3) free samples (Schiffman & Kanuk, 2006), (4) store reputation/ image (Lockshin & Kahrimanis, 1998;Semeijn, Van Riel, & Ambrosini, 2004;Slovic, 2000), (5) product knowledge and information search (Arbuthnot, Slama, & Sissler, 1993;Cox, 1967;Ward, 1996), (6) product/brand loyalty (Kerstetter & Cho, 2004;Lockshin & Spawton, 2001) and (7) product price (Benjamin & Podolny, 1999;Oczkowski, 1994). The application of these relievers is a function of the amount of knowledge (product and store) available to the consumers.…”
Section: Wine Consumers' Risk and Its Managementmentioning
confidence: 99%